Action research processes in a foreign language teaching program: voices from inside - Guerra Sánchez, Juan Carlos; Rodríguez Vásquez, Zoraida; Díaz Mosquera, Claudia Patricia (Colombian Applied Linguistics Journal, 2015)
In this article, we report the final results of a multiple case study that brought together the experiences and reflections of student teachers, cooperating teachers, and advisors about the action research process within the framework of the academic practicum in a foreign language teaching program. Through observations, interviews, focus groups, and research report analyses, the researchers recognized the personal, professional, and political dimensions that guide participants’ teaching and research actions. Findings shed light on issues such as collaboration and engagement to promote conversations that actually connect life in schools and life at the university, and to support continuous learning for teachers. The insights we gained evidenced that the teachers, students, and administrators in the teaching program and their colleagues in the public schools need to strengthen their links through proposals of experiential learning which promote joint efforts, symmetric relationships, and expertise co-construction; thus, enabling all participants to validate their process as individuals, as members of educational institutions, and as key actors in promoting and sustaining a better society.